Bunker Hill : a city, a siege, a revolution - Philbrick, Nathaniel (Viking, 2013)
Recounts the events of the Boston battle that ignited the American Revolution, tracing the experiences of Patriot leader Dr. Joseph Warren, a newly recruited George Washington, and British General William Howe.